Frontiers in biofoundry: opportunities and challenges - Yu, Choo Yee; Ang, Geik Yong; Mat Isa, Nurulfiza; Chan, Kok-Gan (Frontiers in Synthetic Biology, 2025)
Synthetic biology, with its vast potential applications in diverse fields such as biomanufacturing, agriculture, pharmaceuticals, medicine, environment and food industries, is increasingly recognized for its transformative solutions and sustainability potential. This is reflected in the booming of biofoundries in which automation, robotic liquid handling systems and bioinformatics are strategically integrated to streamline and expedite the synthetic biology workflow. The high-throughput capability of biofoundry not only accelerates the discovery pace of synthetic biology but also makes it possible to expand the catalogue of bio-based products that can be produced. In this review, we present the core concept of Design-Build-Test-Learn (DBTL) engineering cycle for biofoundry, early success stories and current challenges in developing a sustainable biofoundry before concluding with future perspectives. Continuous concerted efforts are required to support the planning and establishment of a biofoundry as well as in addressing the gaps and challenges of maintaining a sustainable biofoundry.